Thyroid nodules with indeterminate cytology: prospective comparison between 18F-FDG-PET/CT, multiparametric neck ultrasonography, 99mTc-MIBI scintigraphy and histology. Issue 5 (May 2016) - Piccardo, A; Puntoni, M; Treglia, G; Foppiani, L; Bertagna, F; Paparo, F; Massollo, M; Dib, B; Paone, G; Arlandini, A; Catrambone, U; Casazza, S; et al.
Abstract : Purpose: To evaluate the role of 18 F-flurodeoxiglucose positron emission tomography/computed tomography ( 18 F-FDG-PET/CT) in predicting malignancy of thyroid nodules with indeterminate cytology. Patients and methods: We analysed 87 patients who have been scheduled to undergo surgery for thyroid nodule with indeterminate cytology. All patients underwent 18 F-FDG-PET/CT, multiparametric neck ultrasonography (MPUS), and 99m Tc-methoxyisobutylisonitrile scintigraphy ( 99m Tc-MIBI-scan). Histopathology was the standard of reference. We compared the sensitivity (SE), specificity (SP), accuracy (AC), positive (PPV) and negative predictive (NPV) values of 18 F-FDG-PET/CT with those of 99m Tc-MIBI-scan and MPUS in detecting cancer. Univariate and multivariate analyses evaluated the association between each diagnostic tool and histopathology. Results: On histopathology, 69 out of 87 nodules were found to be benign and 18 to be malignant. The SE, SP, AC, PPV and NPV of 18 F-FDG-PET/CT were 94, 58, 66, 37 and 98% respectively. The SE, AC and NPV of 18 F-FDG-PET/CT were significantly higher than those of MPUS and 99m Tc-MIBI-scan. The association of both positive 18 F-FDG-PET/CT and MPUS (FDG+/MPUS+) showed significantly lower SE (61% vs 94%) and NPV (88% vs 98%) than 18 F-FDG-PET/CT alone, but significantly higher SP (77% vs 58%). On univariate analysis, 18 F-FDG-PET/CT and the combination of FDG+/MPUS+ and of FDG+/MIBI− were all significantly associated with histopathology. On multivariate analysis, only FDG+/MIBI− was significantly associated with histopathology. Conclusion: The AC of 18 F-FDG-PET /CT in detecting thyroid malignancy is higher than that of 99m Tc-MIBI-scan and MPUS. A negative 18 F-FDG-PET/CT correctly predicts benign findings on histopathology. The association of FDG+/MPS+ is significantly more specific than 18 F-FDG-PET/CT alone in identifying differentiated thyroid cancer. A positive 18 F-FDG-PET/CT is significantly associated with malignancy when qualitative 99m Tc-MIBI-scan is rated as negative.